2002
DOI: 10.1177/109019810202900108
|View full text |Cite
|
Sign up to set email alerts
|

Teen Driving Risk: The Promise of Parental Influence and Public Policy

Abstract: An analysis is presented of adolescent driving risk, the advantages of graduated licensing programs, and the potential for parent-based programs to moderate teen driving risks. Risk factors associated with youthful driving illustrate the potential importance and benefits of limiting the amount and conditions under which teens can drive. State policies, such as graduated driver licensing systems that formalize restrictions on youthful driving. have been shown to be effective. However, teen driving risks remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…6,36,[43][44][45] Media campaigns that combine public education and law enforcement are also promising strategies. Finally, engineering strategies, including black boxes for parental review and devices that can mitigate rollover risk and lane departures, could have a significant positive impact on teen driver safety.…”
Section: Discussionmentioning
confidence: 99%
“…6,36,[43][44][45] Media campaigns that combine public education and law enforcement are also promising strategies. Finally, engineering strategies, including black boxes for parental review and devices that can mitigate rollover risk and lane departures, could have a significant positive impact on teen driver safety.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that parents can play a crucial role in reducing the level of teen driving risk (Beck et al, 2002;Preusser et al, 1985;Simons-Morton et al, 2002;. Several investigations (Hartos et al, 2000(Hartos et al, , 2001 have found that teens who report high levels of parental monitoring and driving restrictions are less likely to engage in a variety of risky driving behaviors and to report violations and crashes than are those with fewer restrictions and less monitoring.…”
mentioning
confidence: 92%
“…9 14 20 GDL, however, is largely passive and parents are the true enforcers of GDL policies and any other restrictions on teen driving because they can control access to the car. [21][22][23] Viewed from this perspective, GDL establishes basic restrictions on young drivers and makes restriction normative, which might make it easier for parents to limit initial driving privileges, 24 despite teens intense motivation to drive. 25 In addition, most parents impose modest restrictions on teen driving 23 and parental restrictions are negatively associated with risky driving among young drivers.…”
mentioning
confidence: 99%